Complex-Amplitude-Modulation Vectorial Excitation Beam for High-Resolution Observation of Deep Regions in Two-Photon Microscopy - Matsumoto, Naoya; Watanabe, Koyo; Konno, Alu; Inoue, Takashi; Okazaki, Shigetoshi (Frontiers in Neuroscience, 2022)
In two-photon microscopy, aberration correction is an essential technique for realizing a high resolution in deep regions. A spatial light modulator (SLM) incorporated into an optical system for two-photon microscopy performs pre-compensation on the wavefront of the excitation beam, restoring the resolution close to the diffraction limit even in the deep region of a biological sample. If development on spatial resolution smaller than the diffraction limit is achieved along with aberration correction, the importance of two-photon microscopy for deep region observation will increase further. In this study, we realize such higher resolution observation in the deep region by combining two resolution enhancement methods and an aberration correction method. Therefore, a z-polarizer is added to the aberration-correction optical system, and the SLM modulates the amplitude and phase of the excitation beam; in other words, complex-amplitude modulation is performed. The lateral resolution is found to be approximately 20% higher than the diffraction limit obtained using a circularly polarized beam. Verification was conducted by simulation and experimentation using model samples and ex vivo biological samples. The proposed method has the potential to be effective for live imaging and photostimulation of the deep region of the sample, although it requires only minor changes to the conventional optical system that performs aberration correction.